Therapeutic implications of PD-L1 expression in bladder cancer with squamous differentiation - Morsch, Ronja; Rose, Michael; Maurer, Angela; Cassataro, Maria Angela; Braunschweig, Till; Knüchel, Ruth; Vögeli, Thomas Alexander; Ecke, Thorsten; Eckstein, Markus; Weyerer, Veronika; Esposito, Irene; Ackermann, Maximilian; et al. (BMC Cancer, 2020)
BACKGROUND: Immune checkpoint inhibitors (ICI) are an integral part of bladder cancer therapy, however, the relevance of ICI treatment for mixed and pure squamous cell carcinoma of the bladder remains poorly studied. Therefore, we analysed the expression of programmed death-ligand 1 (PD-L1) in urothelial carcinomas with squamous differentiation (UC/SCC) and pure squamous cell carcinoma (SCC) of the bladder and studied a UC/SCC patient with ICI therapy. METHODS: Tissue microarrays of 45 UC/SCC and 63 SCC samples were immunohistochemically stained with four anti-PD-L1 antibodies (28-8, 22C3, SP142 and SP263). PD-L1 expression was determined for tumour cells (TP-Score), immune cells (IC-Score) and combined (CPS, combined positive score). In addition, we present clinical and histological data of an UC/SCC patient with nivolumab therapy. RESULTS: Overall, positive PD-L1 staining ranged between 4.8 and 61.9% for IC and 0 and 51.2% for TC depending on the used antibody. There were no significant differences between UC/SCC and SCC. According to current FDA guidelines for example for first line therapy of urothelial cancer with pembrolizumab (CPS ≥ 10), a subset of SCC patients up to 20% would be eligible. Finally, our UC/SCC index patient revealed excellent therapy response regarding his lung metastasis. CONCLUSIONS: Our data reveal a PD-L1 expression in squamous differentiated carcinomas comparable with current data shown for urothelial tumours. In accordance with the encouraging clinical data of the index patient we suggest ICI treatment also for mixed and pure SCC of the urinary bladder.
CRIS-Team Scopus Importer:2020-03-31
Keywords: Bladder cancer; Immunotherapy; PD-L1; Squamous cell carcinoma